Pelatihan dan Simulasi Mitigasi Bencana bagi Siswa SMPN 2 Kuala Simpang - Teuku Hasan Basri; Nuraini Nuraini (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
This article aims to discuss disaster mitigation training and simulation for students of SMPN 2 Kuala Simpang. Disasters can occur at any time without knowing when the disaster will occur, both non-natural disasters and natural disasters, non-natural disasters such as fire, Covid-19, war and others that are non-natural, while natural disasters such as volcanic eruptions, earthquakes, tsunamis, floods and landslides. So to anticipate disaster mitigation, it is necessary to carry out simulations and training for junior high school students. The solutions for this service are: (1) Providing alternative solutions for students in overcoming disasters that have arisen in the Aceh Tamiang region. (2) Teaching directly how training and simulations in dealing with disasters that will occur in the Aceh Tamiang area for students of SMPN 2 Kuala Simpang. The results of the discussion are that the socialization of disaster mitigation provides an alternative in understanding students so that they can know how to deal with disasters such as floods, earthquakes and others that often occur in the area, students and teachers better understand how to deal with disaster mitigation and related first aid in dealing with a disaster that occurs and how to deal with disaster mitigation awareness and the lack of knowledge of teachers and students in knowing how to deal with natural disasters and limited communication tools at SMPN 2 Kuala Simpang School and in general students and teachers around do not have access to handling disaster mitigation at school.